UPAYA WARGA SEKOLAH DALAM MENCEGAH DEGRADASI MORAL SISWA - Ahmadi, Ahmadi; Siti, Mutmainnah (Universitas Al-Amien Prenduan, 2021)
The delinquency of school-age children or adolescents who are attending school is not only troubling for parents and society, but also for teachers at school. Student delinquency is not just a matter of parents and society alone. But it is also a problem for schools, because schools as formal educational institutions are considered to be the most responsible for educational outcomes including the character of a child (student). Therefore it needs attention and efforts to prevent early moral degradation of students. This research uses a descriptive qualitative approach to try to reveal the principal's efforts to prevent the moral degradation of students at MTs At-Taufiqiyah. The research subjects were school principals, BP/BK teachers, student teachers, Akidah Ahlak teachers, and students. From the results of the study it can be concluded that school members contribute to each other in preventing the moral degradation of students at MTs. At-Taufiqiyah Aeng Baja Bluto. This effort is carried out by providing direct guidance to students. cooperate with foundation administrators, teacher boards and student guardians in instilling religious moral values, providing religious understanding and moral inculcation, and educating students to serve their parents.